1990
DOI: 10.1111/j.1399-3054.1990.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial interaction between photosynthesis and respiration in mesophyll protoplasts of pea during short light‐dark cycles

Abstract: The respiratory uptake or photosynthetic evolution of oxygen by mesophyll protoplasts of pea (Pisum sativum L. cv. Arkel) were monitored during successive short. (3–5 min) cycles of darkness and illumination. The rate of respiration was nearly doubled after 3–4 short periods of illumination while there was a 15–20% enhancement in photosynthesis with cycles of illumination and darkness preceding illumination. Such interaction between photosynthesis and respiration was statistically significant when bicarbonate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…We have recently reported that the processes ofphotosynthesis and respiration are mutually beneficial (20). The movement of phosphoglycerate/dihydroxyacetone phosphate and oxalacetate/malate between the chloroplasts, cytosol, and mitochondria may help to maintain a favorable balance of adenine and pyridine nucleotides in these organelles for their optimal performance (10,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that the processes ofphotosynthesis and respiration are mutually beneficial (20). The movement of phosphoglycerate/dihydroxyacetone phosphate and oxalacetate/malate between the chloroplasts, cytosol, and mitochondria may help to maintain a favorable balance of adenine and pyridine nucleotides in these organelles for their optimal performance (10,23).…”
Section: Discussionmentioning
confidence: 99%
“…Illumination was provided at an intensity of 50 ME m-2 s-5. The plasmolyzed leaf pieces were then digested in Petri dishes with Cellulase Onozuka R-10 and Macerozyme R-I0 (Yakult Honsha, Nishinomiya, Japan), as described in detail elsewhere (20). The preparation had about 90 to 95% intact protoplasts, as indicated by the uptake of neutral red and exclusion of Evans blue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports established that the oxidative metabolism in mitochondria has a beneficial and essential role in the photosynthetic process as well (12,13,28). It is possible that the marginal interference by respiratory inhibitors of photosynthetic metabolism (Table II) makes protoplasts highly susceptible to photoinhibitory light.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports establish that there is a rapid and strong interaction between respiration and photosynthesis in plant tissue. Respiratory metabolism is beneficial for photosynthesis in the plant cell, as shown in leaves and protoplasts (12,13,28). The rate of dark respiration in leaves is increased after prolonged illumination and is presumed to be one of the long-term effects of photosynthesis.…”
mentioning
confidence: 99%